The Significance of Kurdish Scientists to Mental Science during The Manuscript of Mullah Ibrahim Al-Kurani - ئەحمەد پشدەري عابد (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
Indeed, the mosques and schools were the center of teaching and learning until middle of the last century, in all Kurdistan areas. Moreover, hundreds of religious scholars, politicians, writers and poets had a great role of giving momentum to scientific movements in Kurdish society. In these schools, all different sciences were taught while students spent many years to learn them. However, it can be seen that the Kurdish Muslim scholars focused on the rational sciences, such as logic, kalam and philosophy more than others.